PFM.13 Guidelines on Fetal Growth Restriction – A Comparison of Recent National Publications. (9th June 2014) - Unterscheider, J; O'Donoghue, K; Malone, FD
Abstract : Objective: To review, compare and contrast recommendations from national, recently published clinical practice guidelines for pregnancies complicated by fetal growth restriction (FGR). Methods: Clinical guidelines informing best practice management of FGR pregnancies issued by the American Congress of Obstetricians and Gynaecologists, the Society of Obstetricians and Gynaecologists of Canada and the Royal College of Obstetricians and Gynaecologists in the UK are reviewed together with the currently published literature on this topic. Results: All guidelines were published in 2013; while this is the first national guideline on FGR in Canada, it took the respective colleges in the UK and USA 11 and 13 years to update their guidance on FGR. Each of the guidelines uses different terminology to describe pregnancies affected by suboptimal fetal growth; all of them agree that an EFW <10 th centile should alert clinicians to small fetal size. All guidelines describe risk factor screening for improved detection of FGR and acknowledge the limited accuracy achieved with fundal height measurement. No agreement is reached over the value of fetal weight customisation. All colleges have varied opinions regarding methods of Doppler surveillance however agree that umbilical artery Doppler is beneficial as primary surveillance tool. Conclusions: Results of this review relay significant inconsistencies and call for an urgent international consensus on this important and common clinical topic. Current data is used to develop a clinical practice guideline for Ireland, which will be presented in context with this review.